Think Again: First Do No Harm A Case of Munchausen Syndrome by Proxy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Apparent life-threatening events caused by Munchausen syndrome by proxy (MSP) are rare but difficult to resolve medically. Failure to properly diagnose MSP can lead to further abuse by the caregiver and increase the risk of complications due to long hospital stays and invasive tests. In this paper, we describe our experiences with a baby who ended up being diagnosed with MSP, including our initial failure to find a pathology, delay of MSP diagnosis, our growing suspicion of MSP despite technical setbacks, our actions after we confirmed MSP as the cause of his hospitalizations. We also describe the difficulties of diagnosing MSP compared to more traditional problems and explain a series of precautions and guidelines to help detect it in a timely manner.
Keywords: Munchausen by proxy; apnea; medical abuse; LIFE-THREATENING EVENTS; CHILD-ABUSE; INFANTS